Hitchcock's Magic. - Badmington, Neil (University of Wales Press, 2011)
Why are we drawn to the work of Alfred Hitchcock so long after his final film appeared? What is the source of Hitchcock's magic? This book answers these questions by focussing upon the films themselves, upon how they hold our attention by constantly withholding something from us. Combining close analysis of a number of Hitchcock's most famous films with more general discussion his work, the volume takes issue with the biographical and psychoanalytic approaches that have dominated studies of Hitchcock's films to argue instead for the significance of textuality.